Dinamika Kehidupan Beragama Kaum Nahdiyin-Salafi di Pamekasan Madura - Nor Hasan (Islamica: Jurnal Studi Keislaman, 2013)
In principle, the Salafi-Islam attempts to call for genuine Islamic teaching as practiced during the period of the Prophet. Salafi-Islam came to Indonesia in the late nineteenth and early twentieth centuries, then spread to different places in the Archipelago. In Larangan, Pamekasan, the spread of Salafi-Islam is still in its nascent stage, from person-to-person, and appears as a small phenomenon in the midst of predominantly mainstream Islam. Salafi teachings spread through different forms of communication media (radios, televisions, magazines, and books) and religious practices of its ?proponents. The movement manifests itself in the pratices of rituals, not in politics. The implication of encounter between salafi-Islam and NU as the mainstream religious group in Pamekasan is as follows: (1) religous life in Pamekasan becomes more dynamic; (2) there emerges inward-looking attitude at their own religous practices as well as outward-looking attitude to the others. This phenomenon can be observed among more educated members of the society. Among the common people, however, there are two types of attitude: ignorance and negative reaction; and (3) an attempt to search for the common ground and dialogue among different religious communities is being conducted.